2009
DOI: 10.1111/j.1440-1797.2008.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

Early renal post‐ischaemic tissue damage and dysfunction with contribution of A1‐adenosine receptor activation in rat

Abstract: These findings suggest that endogenous activation of A(1)-AR contributes to the early development of renal ischaemia/reperfusion injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 18 publications
1
26
1
Order By: Relevance
“…The renal I/R-induced tubular cell death, loss of tight junction integrity and cell polarity, shedding of brush borders and exfoliation of viable cells led to disturbed Na + reabsorption (Devarajan, 2006;Moosavi et al, 2009) and increases in FE Na by 6.7-fold in the BIR-V group, 4.3fold in the BIR-P group and 2.7-fold in the BIR-A group compared to that of the sham group, while the disturbed Na + reabsorption along with reduced GFR and hence filtered-load of Na + caused U Na V • not to change in any of the ischaemic groups. However, there were falls in F I G U R E 7 Representative light micrographs of the renal inner medullary cross section at the end of a 2 h reperfusion period following 30 min bilateral clamping of renal artery (BIR-A group), vein (BIR-V group) and pedicle (BIR-P group), as well as equivalent periods in the sham group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The renal I/R-induced tubular cell death, loss of tight junction integrity and cell polarity, shedding of brush borders and exfoliation of viable cells led to disturbed Na + reabsorption (Devarajan, 2006;Moosavi et al, 2009) and increases in FE Na by 6.7-fold in the BIR-V group, 4.3fold in the BIR-P group and 2.7-fold in the BIR-A group compared to that of the sham group, while the disturbed Na + reabsorption along with reduced GFR and hence filtered-load of Na + caused U Na V • not to change in any of the ischaemic groups. However, there were falls in F I G U R E 7 Representative light micrographs of the renal inner medullary cross section at the end of a 2 h reperfusion period following 30 min bilateral clamping of renal artery (BIR-A group), vein (BIR-V group) and pedicle (BIR-P group), as well as equivalent periods in the sham group.…”
Section: Discussionmentioning
confidence: 99%
“…The sum of all numerical scores in each group was taken as the total histopathological score Moosavi, Bayat, Owji, & Panjehshahin, 2009). Sections were subjected to routine staining with haematoxylin and eosin.…”
Section: Renal Histopathological Examinationsmentioning
confidence: 99%
“…DPCPX inhibits the effect of adenosine on Adora1 by specifically binding to this receptor. DPCPX was used under in vitro and in vivo conditions to evaluate the role of Adora1 in the lungs (Factor et al , 2007), brain (Ilie et al , 2009), gut (Brunsden and Grundy, 1999), heart and kidney (Moosavi et al , 2009). Preliminary experiments revealed that antagonism of Adora1 activity result in a reduction in ERK1/2 phosphorylation (data not shown), which is critical for E2-mediated cell growth (Keshamouni et al , 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The protective mechanism of methylxanthines in the initiation phase of renal injury following ischemia-reperfusion is likely related at least in part to inhibition of vasoconstrictive adenosine receptors. Support for this notion comes from a recent study in which the A1 adenosine receptor antagonist DPCPX infused prior to and following a 30 min period of bilateral renal artery obstruction was observed to significantly improve creatinine clearance over the initial 4 hours following reperfusion (Moosavi et al 2009). Furthermore, the immediate postischemic reduction of GFR was enhanced by dipyridamole, an inhibitor of adenosine uptake through equilibrative nucleoside transporters, and this effect was abrogated by theophylline (Lin et al 1987).…”
Section: Disease and Therapeutic Aspectsmentioning
confidence: 99%